2013
DOI: 10.1111/1365-2664.12153
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW: Refuges for fauna in fire‐prone landscapes: their ecological function and importance

Abstract: Summary1. Rapid environmental change is placing increasing pressure on the survival of many species globally. Ecological refuges can mitigate the impacts of change by facilitating the survival or persistence of organisms in the face of disturbance events that would otherwise lead to their mortality, displacement or extinction. Refuges may have a critical influence on the successional trajectory and resilience of ecosystems, yet their function remains poorly understood. 2. We review and describe the role of ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
143
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(144 citation statements)
references
References 85 publications
0
143
0
1
Order By: Relevance
“…Many invasive species take opportunistic advantage of habitat modification and therefore increase their overall impact within these habitats (Didham et al 2005;Janssen et al 2007;McGregor et al 2014;McDonald et al 2016;Hradsky et al 2017). In many cases structurally complex habitats have been shown to decrease predation risk by providing refuges or shelter for prey, reducing encounter rates between predator and prey, hindering foraging activity of predators and reducing predator kill rate success (Fischer & Lindenmayer 2007;Janssen et al 2007;Robinson et al 2013;McGregor et al 2014;Hradsky et al 2017). A study conducted in northern Australia by McGregor et al (2014) on the interactive effects between habitat modification and potential predator pressure found that modifications of habitat produced by grazing, and particular fire types, have strong effects on feral cat movement behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Many invasive species take opportunistic advantage of habitat modification and therefore increase their overall impact within these habitats (Didham et al 2005;Janssen et al 2007;McGregor et al 2014;McDonald et al 2016;Hradsky et al 2017). In many cases structurally complex habitats have been shown to decrease predation risk by providing refuges or shelter for prey, reducing encounter rates between predator and prey, hindering foraging activity of predators and reducing predator kill rate success (Fischer & Lindenmayer 2007;Janssen et al 2007;Robinson et al 2013;McGregor et al 2014;Hradsky et al 2017). A study conducted in northern Australia by McGregor et al (2014) on the interactive effects between habitat modification and potential predator pressure found that modifications of habitat produced by grazing, and particular fire types, have strong effects on feral cat movement behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of refuges in facilitating survival will vary between species and is dependent on whether refuges provide critical resources that are absent from the surrounding landscape (Robinson et al 2013). Fire refuges may be especially important for fauna that are dependent on mature vegetation features, such as tree hollows for nesting or denning (Banks et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of fire have been documented in some species of Antechinus, none have possessed a range as small as the type population of A. argentus. Furthermore, the present-day threat of habitat fragmentation likely means that the impact of fires are potentially greater than in the evolutionary history of species (Robinson et al, 2013). The general use of "patchy" fire mosaics for the conservation of animal species dominates the literature (e.g., Bradstock et al, 2005, Christensen and Kimber, 1975, Woinarski, 1999.…”
Section: Outline Of the Present Studymentioning
confidence: 99%
“…The Australian fauna have adapted to the destructive effects of fire in part by seeking refuge in surrounding habitat (Robinson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%